2015
DOI: 10.1039/c5sc02728d
|View full text |Cite
|
Sign up to set email alerts
|

A carbon–carbon hybrid – immobilizing carbon nanodots onto carbon nanotubes

Abstract: The thrust of this work is to integrate small and uniformly sized carbon nanodots (CNDs) with single-walled carbon nanotubes of different diameters as electron acceptors and electron donors, respectively, and to test their synergetic interactions in terms of optoelectronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 39 publications
3
43
1
Order By: Relevance
“…[25] Thec ovalent approach to CNDs functionalization is particularly interesting as it enables the introduction of multiple photo-or electroactive units in the form of stable nanoconjugates.I nt his context, we have explored the preparation of novel CND-based electron donor-acceptor systems.Inparticular,wehave covalently linked aphoto-and redox-active molecular building block, namely p-extended tetrathiafulvalene (exTTF), [26] to CNDs materials.exTTFs are pro-aromatic electron donors.U nlike porphyrins,t hey undergo ar emarkable gain of aromaticity and planarity upon oxidation, forming stable one-electron and two-electron oxidized species at relatively low oxidation potentials.C onsidering these features,e xTTFs have been widely used to form electroactive architectures when linked to fullerenes, carbon nanotubes,a nd graphene. [20][21][22][23] Aconstant pressure during the microwave synthesis leads to ad istribution of pressuresynthesized CNDs (pCNDs) with as harp and narrow emission pattern. [29] We have synthesized the starting CNDs by using citric acid and urea precursors by following the recently published procedure by some of us.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Thec ovalent approach to CNDs functionalization is particularly interesting as it enables the introduction of multiple photo-or electroactive units in the form of stable nanoconjugates.I nt his context, we have explored the preparation of novel CND-based electron donor-acceptor systems.Inparticular,wehave covalently linked aphoto-and redox-active molecular building block, namely p-extended tetrathiafulvalene (exTTF), [26] to CNDs materials.exTTFs are pro-aromatic electron donors.U nlike porphyrins,t hey undergo ar emarkable gain of aromaticity and planarity upon oxidation, forming stable one-electron and two-electron oxidized species at relatively low oxidation potentials.C onsidering these features,e xTTFs have been widely used to form electroactive architectures when linked to fullerenes, carbon nanotubes,a nd graphene. [20][21][22][23] Aconstant pressure during the microwave synthesis leads to ad istribution of pressuresynthesized CNDs (pCNDs) with as harp and narrow emission pattern. [29] We have synthesized the starting CNDs by using citric acid and urea precursors by following the recently published procedure by some of us.…”
mentioning
confidence: 99%
“…By virtue of variable supramolecular forces either electron donors or acceptors have been non-covalently combined with CNDs. [16,[20][21][22][23] Thec ovalent decoration of CNDs with photoand electro-active building blocks has only recently been explored with porphyrins, [24] where the strong electronic interaction with CNDs results in as eries of energy transfer and charge transfer events. [25] Thec ovalent approach to CNDs functionalization is particularly interesting as it enables the introduction of multiple photo-or electroactive units in the form of stable nanoconjugates.I nt his context, we have explored the preparation of novel CND-based electron donor-acceptor systems.Inparticular,wehave covalently linked aphoto-and redox-active molecular building block, namely p-extended tetrathiafulvalene (exTTF), [26] to CNDs materials.exTTFs are pro-aromatic electron donors.U nlike porphyrins,t hey undergo ar emarkable gain of aromaticity and planarity upon oxidation, forming stable one-electron and two-electron oxidized species at relatively low oxidation potentials.C onsidering these features,e xTTFs have been widely used to form electroactive architectures when linked to fullerenes, carbon nanotubes,a nd graphene.…”
mentioning
confidence: 99%
“…Considering the lack of spectroscopic signature for the CND radical cation, the current generation process was followed via the evolution of the CND ground state bleaching at 465 nm. 17,18 The respective kinetics are best fit tri-exponentially with lifetimes on the order of 1, 10, and 1000 ps for all measurements - Table 1. The short and intermediate lifetimes, that is, 1 and 10 ps, are attributed to non-radiative recombination, population of trap states, and charge carrier injection.…”
Section: Conceptual Insightsmentioning
confidence: 87%
“…[12][13][14][15] We have seen that CNDs are prone to undergo photoinduced charge-transfer in nanohybrid materials, indicating that they are also suitable as photoactive components. [16][17][18] Indeed, several studies have shown that the principle of using such materials as sensitizers in mesoscopic solar cells is sound, although the reported power conversion efficiencies cannot yet compete with inorganic QD solar cells. [19][20][21][22][23][24] We here classify GQDs as structurally well-defined, carbonrich organic molecules that generally require multi-step synthetic procedures in contrast to CNDs, which are usually synthesized in a single step but do not exhibit a well-defined molecular structure.…”
Section: Conceptual Insightsmentioning
confidence: 99%
“…Polyacrylic acid sodium salt (PAAS), ethylene diamine tetraacetic acid (EDTA), D-(+)-glucose, sucrose and guanidine hydrochloride were purchased from Sigma-Aldrich (USA). AgNO 3 Apparatus and Software. CL signals were acquired by using a BPCL ultra-weak CL analyzer (Biophysics Institute of the Chinese Academy of Science in China) equipped with a CR-105 photomultiplier tube (PMT) (Hamamatsu, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%